Антология выдающихся достижений в науке и технике. Часть 4: Изобретение химических взрывчатых веществ - Баранов, М.И. (Електротехніка і електромеханіка, 2011)
A brief outline from the global history of invention of chemical explosives widely applied to solving military-engineering and national-economy tasks is given.